THE ETYMOLOGY OF PUBLIC SPACE- EXPLORING CRAFTING COMMUNITY SPACES - Chhabra, Pankaj; Shukla, Amrita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The nature of public space has changed over the time period. Its role evolved and developed as per the requirement, context, and culture of people. Public space development is an art of creating a connection between the city and people. A city without public spaces creates a city without culture and history. Public space directly contributes for socio, the economic and environmental development of the city. Its traces can be found from Agora’s in the Greek period to parks and squares in contemporary times. Public spaces have been focal point of the city in past, but they lost their attention during modern urban development. It acts as a stage for translation of art and the drama of city life. Different experts from various fields have introduced different terminologies to explain the same and much work is done on the environmental and economic dimensions of sustainability. In contrast, the social dimension is yet to be explored. The public space directly contributes to social sustainability thus, it’s essential to understand and integrate the concept of public space in the present time. In developing countries, the shortage of public space can be addressed by its effective utilization and the city’s identity can be restored by developing an association between the city and people through publicness criteria identified in the study. The intent of the study is to provide a solution to fill the social gap created during modernism and technological advancement by taking references from the past.